2017
DOI: 10.3892/etm.2017.4638
|View full text |Cite
|
Sign up to set email alerts
|

Expression of prostate stem cell antigen is downregulated during flavonoid-induced cytotoxicity in prostate cancer cells

Abstract: Abstract. Prostate stem cell antigen (PSCA) is expressed in the majority of prostate cancer cases and may be a potential therapeutic target in the treatment of prostate cancer. The present study evaluated the cytotoxicity of three flavonoids (genistein, luteolin and quercetin) towards DU145 prostate cancer cells, and investigated the effect of these flavonoids on PSCA expression. The results demonstrated that genistein, luteolin and quercetin inhibited the growth of DU145 cells in a dose-dependent manner (P<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Quercetin decreases the viability and proliferation of MCF-7 breast cancer cells through apoptosis activation, via increasing the levels of Bcl-2-associated X protein (BAX) and caspase-3 expression and decreasing Bcl-2 expression. In addition, quercetin activates necroptosis, via increasing the levels of receptor-interacting serine/threonine-protein kinase 1 (RIPK1) and receptor-interacting serine/threonine-protein kinase 3 (RIPK3) expression [20,21]. Both luteolin and quercetin were tested in prostate cancer cells DU145, showing cell cycle arrest [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin decreases the viability and proliferation of MCF-7 breast cancer cells through apoptosis activation, via increasing the levels of Bcl-2-associated X protein (BAX) and caspase-3 expression and decreasing Bcl-2 expression. In addition, quercetin activates necroptosis, via increasing the levels of receptor-interacting serine/threonine-protein kinase 1 (RIPK1) and receptor-interacting serine/threonine-protein kinase 3 (RIPK3) expression [20,21]. Both luteolin and quercetin were tested in prostate cancer cells DU145, showing cell cycle arrest [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, quercetin activates necroptosis, via increasing the levels of receptor-interacting serine/threonine-protein kinase 1 (RIPK1) and receptor-interacting serine/threonine-protein kinase 3 (RIPK3) expression [20,21]. Both luteolin and quercetin were tested in prostate cancer cells DU145, showing cell cycle arrest [21]. Other compounds of Stevia pilosa and Stevia eupatoria include β-sitosterol and stigmasterol, which have an antiproliferative effect by activating the extracellular receptor kinase (ERK) 1/2 pathway, and apoptosis induction, decreasing Bcl-2 expression and increasing BAX expression in breast cancer cells MDA-MB-231 [22].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of prostate stem cell antigen (PSCA) has been observed in more than 80% of prostate cancer tissues and all cases of bone metastatic prostate cancer in patients. Importantly, the treatment with genistein together with other two flavonoids belonging to the class of flavones (luteolin) and flavonols (quercetin) inhibited the expression of PSCA at the mRNA and protein level in prostate cancer DU145 cells [ 100 ].…”
Section: Targeting Metastatic Cancermentioning
confidence: 99%
“…Consequently, addition of a polar cosolvent is imperative. Probed copolar solvents include water, methanol, ethanol, and mixtures of diverse proportions of these solvents (Yoda et al acid; pyrogallol; tricaffeoylquinic acid; 3,4,5-tricaffeoylquinic acid; 1,3,5-tricaffeoylquinic acid; rutin; 3-feruloyl-5-caffeoylquinic acid; 4-caffeoyl-5-feruloylquinic acid; 3.5-dicaffeoylquinic acid (isochlorogenic acid A); 1,4-dicaffeoylquinic acid; 3,4-dicaffeoylquinic acid (isochlorogenic acid B); 1,3-dicaffeoylquinic acid; 4,5-dicaffeoylquinic acid (isochlorogenic acid C); quercetin-3-Oglycoside; galuteolin; quercetin; roseoside; 3-feruloylquinic acid; 5-feruloylquinic acid; 4-caffeoylquinic acid (cryptochlorogenic acid); 3-caffeoylquinic acid (chlorogenic acid); 4 2020) observed that LC-MS/MS analysis was not that much reliable when it comes to quantification of phenols. The reason is that the method requires many chemicals as standards since there are many polyphenolic isomers.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…According to Zhang et al [4] The immune system carries out inflammatory response upon the invasion by foreign bodies. There is a production of free radicals which destroy foreign bodies.…”
Section: Health-promoting Activity Of Stevia Phenolic Compoundsmentioning
confidence: 99%